Resilience among young mothers affected by HIV in South Africa: Adaptations and psychometric properties of the Child and Youth Resilience Measure-Revised (CYRM-R) in a large cohort - Wylene Saal; Angelique Thomas; Christina Laurenzi; Hlokoma Mangqalaza; Jane Kelly; Janke Tolmay; Vuyolwetu Tibini; Elona Toska (Elsevier, 2023)
Background: While growing evidence has documented risks and resilience to HIV and poor sexual and reproductive health (SRH) among young women, young mothers' abilities to respond to and overcome challenges have been understudied. Developing appropriate methodologies to measure resilience in the context of HIV, especially among young mothers, is a critical first step to filling this gap. We aimed to improve the relevance, and comprehensibility of an open-access resilience measure for use among young mothers living in HIV-endemic communities in South Africa. This paper summarizes a two-stage study that was carried out in the Eastern Cape, South Africa. Methods: First, n = 9 cognitive interviews were conducted to inform the adaptation of the Child and Youth Resilience Measure Revised (CYRM-R) for use among young mothers (n = 7 living with HIV). The adapted measure was applied in remote interviews with 892 adolescent mothers during the COVID-19 pandemic (December 2021-April 2023). We investigated the basic psychometric properties of the adapted measure using STATA16. Results: Cognitive interviews offered unique perspectives on how to modify items in English and isiXhosa, including items that had similar understandings and responses, with new probes and additional key words added to seven items. Participants' understanding of item wording and the translation of items resulted in word changes or substitution to maximise participants' understanding of eight out of 17 items. The utilization of vignettes proved to be useful in engaging participants to reflect on their experiences. The revised scale had moderate psychometric properties. The EFA confirmed a two-factor structure, and the internal consistency of the CYRM-R was moderate (α = 0.75; ω = 0.75). Conclusion: Cognitive interviews supported the adaptation of a resilience measure for adolescent mothers affected by HIV in South Africa. Initial psychometric properties highlight possible further adaptations needed, potentially due to the unique population of adolescent mothers.